Magnitude of episiotomy practice and associated factors among women who gave birth at Hiwot Fana Specialized University Hospital, Eastern Ethiopia - Bekele, Habtamu; Tamiru, Dawit; Debella, Adera; Getachew, Alemeshet; Yohannes, Ephrem; Lami, Magarsa; Negash, Abraham; Asfaw, Henock; Ketema, Indeshaw; Eyeberu, Addis; Habte, Sisay; Eshetu, Bajrond; et al. (Frontiers in Global Women's Health, 2022)
Abstract Background: Episiotomy is an intentional surgical incision made on the perineum with the aim of enlarging the introits during second stage of labor or just before delivery of the baby. Episiotomy also interferes with the mother’s comfort during the postpartum period and has associated complications especially when it is done without proper medical indication. However, episiotomy has become one of the misused obstetric interventions in many lower income settings. Objective: This study aimed to determine the magnitude of episiotomy practice and associated factors among women who gave birth at Hiwot Fana specialized university hospital, Harar, Eastern Ethiopia, 2021. Method: Facility-Based cross-sectional study was conducted among 408 systematically selected mothers who gave birth at Hiwot Fana specialized university hospital, Harar, from January 1, 2021, to December 30,2021. Data were collected from delivery medical records using a standard extraction checklist. The extracted data were checked, coded, and entered into Epi-data version 3.1 and exported to STATA version 16 software for analysis. Logistic regression was fitted to identify factors associated with episiotomy practice. P-values less than 0.05 were considered to declare the presence of statistical significance. Result: The overall prevalence of episiotomy practice was found to be 43.4%( 95% CI: 38.7, 48.9), Medio lateral was the most commonly practiced episiotomy(41.4%). Parity (AOR:6.2; 95% CI 3.8 - 17.6), 1st minute Apgar score (AOR:1.6; 95% CI 1.04 - 2.67), and Presence of maternal medical conditions(AOR:3.3; 95% CI 1.09 -6.9) and induced onset of labor(AOR:1.6; 95%CI 1.12, 4.13) were significantly associated with episiotomy practice. Conclusion: The prevalence of episiotomy practice in the study area is higher than the recommended practice by WHO. Parity, medical condition, onset of labor and 1st min APGAR score were significant factors for episiotomy practice. Considering the presence of appropriate medical indication or preventing unjustifiable case selection especially on mothers who are nulliparous ,with existing medical condition or on labor induction may help reduce the current high practice rates.